Shock waves underlie efficient desalination process. Issue 4 (April 2016) - Bazant, Martin
Abstract : A technique that exploits deionisation shock-waves in porous media to purify water is under development by researchers in the USA at the Massachusetts Institute of Technology. In the new process, called shock electrodialysis, water flows through a porous material – in this case, made of tiny glass particles, or frit – with membranes or electrodes sandwiching the porous material on each side.